2018
DOI: 10.1002/ijc.31819
|View full text |Cite
|
Sign up to set email alerts
|

HPV‐mRNA and HPV‐DNA detection in samples taken up to seven years before severe dysplasia of cervix uteri

Abstract: Randomized clinical trials using human papillomavirus (HPV) DNA testing have found increased protection against cervical cancer and HPV-based screening is globally recommended for women ≥30 years of age. HPV-mRNA is a promising alternative target for cervical screening tests, but assessing equivalence requires longitudinal evaluation over at least the length of a screening interval. Our aim is to analyze the longitudinal sensitivity of HPV-mRNA and HPV-DNA in cervical samples taken up to 7 years before severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 16 publications
1
41
0
1
Order By: Relevance
“…That study also found no significant difference in longitudinal negative predictive value of mRNA and DNA tests. Also a Swedish retrospective study showed similar long term sensitivity for mRNA and DNA assays at least up to 7 years …”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…That study also found no significant difference in longitudinal negative predictive value of mRNA and DNA tests. Also a Swedish retrospective study showed similar long term sensitivity for mRNA and DNA assays at least up to 7 years …”
Section: Discussionmentioning
confidence: 81%
“…Also a Swedish retrospective study showed similar long term sensitivity for mRNA and DNA assays at least up to 7 years. 14 Nevertheless, it is worth to note that the mRNA assay targets a step ahead than HPV-DNA in the natural history of the disease, thus the duration of reassurance following a mRNA negative test can be only lower than, if not equal to, that of a negative DNA test. If the differentiation of productive nononcogenic infections and abortive potentially oncogenic infections occurred very early in the natural history of the infection, the difference in the duration of the protection between the two tests would be very small.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The proposed resource not only will enable the discovery and validation of new biomarkers, but also will be useful for studies on equivalence of new variants of previous tests. An example is a recent validation study where an HPV test based on detection of HPV mRNA was found to have an equivalent performance to tests based on the detection of HPV DNA over a 7-year follow-up (Forslund et al, 2019). The study was based on a large biobank collected more than 7 years ago that had been followed up with registry linkagesand thus did not have to wait prospectively for 7 years to obtain longterm follow-up data.…”
Section: Furthering a Research Infrastructure For Biomarker Discoverymentioning
confidence: 99%